FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA JURUSAN AKUNTANSI - Andri Novius (STIE Pelita Nusantara Semarang, 2012)
This research is to investigate wether internal and external factores, and learning approach effected to undergraduate’s study on accounting program, especially on accounting’s core of study. The population in this research is undergraduate accounting program in Universitas Islam Negeri Suska Riau. At the purposive sampling technique base, then 43 sampels can be used. The result shows that internal factors and external factor did not effetctstudy achievement. This is due to the lack of “will” from the student itself for learning and lack of motivation from external factor. Thus, learning approach factor effected to study achievement of the undergraduate student.